The Relevance of Hermeneutics to Yusuf Al-Qaradhâwî’s Understanding in Formulating Islamic Law Based on the Prophet ﷺ’s Hadith - Engkos Kosasih; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2024)
The universalism of Islamic teachings, which are based on the text of the Koran and Hadith and are always in line with contemporary developments, must be supported by contextual understanding as well as textual understanding. This includes the application of a hermeneutic perspective, which aims to interpret, comprehend, and translate the true reality concealed within the text. This study intends to investigate the applicability of hermeneutics to Yusuf Al-Qaradhâwî's understanding of formulating Islamic law from the Prophet ﷺ's hadiths, in addition to conducting a comparative and thematic analysis of other scholars' hermeneutic interpretations. The study employs a qualitative research methodology, theme analysis, and literature review techniques to examine Al-Qaradhâwî's writings on the hadith of the Prophet ﷺ. The contextual and historical factors that shaped his comprehension of the hadith are emphasized. The analysis's findings demonstrate that Yusuf Al-Qaradhâwî's comprehension is essentially similar to that of traditional hadith scholars. Nonetheless, he provides thoughtful and practical approaches and ideas for comprehending the Prophet's sunnah in a contextual and all-encompassing manner. It is intended that the findings of this study will make a significant contribution to raising scholarly awareness of the applicability of hermeneutics in this situation. In addition, it can be a valuable source of information for future research aimed at understanding Islamic law originating from the hadith of the Prophet ﷺ.